2022
DOI: 10.1111/apt.17352
|View full text |Cite
|
Sign up to set email alerts
|

Severe colitis in patients with melanoma treated with BRAF/MEK inhibitors

Abstract: Summary Background and Aims Dual blockade of BRAF and MEK kinases is a standard of care for metastatic V600E/K BRAF mutant melanoma. This study reports the first systematic description of colitis due to BRAF and MEK inhibitors. Methods We studied consecutive patients with melanoma, treated with BRAF and MEK inhibitors, who had colitis requiring hospitalisation. Electronic files were studied; endoscopic biopsies and colectomy specimens were read centrally. Results Between January 2021 and March 2022, nine women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Carbonnel et al [10] reported the largest series of 10 patients with advanced melanoma who had severe BRAF/MEKi-related colitis requiring hospitalization. Nine patients were treated with encorafenib and binimetinib and 1 patient with dabrafenib and trametinib.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonnel et al [10] reported the largest series of 10 patients with advanced melanoma who had severe BRAF/MEKi-related colitis requiring hospitalization. Nine patients were treated with encorafenib and binimetinib and 1 patient with dabrafenib and trametinib.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonnel et al have reported a series of 10 consecutive patients hospitalised in their centre for severe colitis related to treatment with a combination of BRAF and MEK inhibitors for metastatic melanoma 6 . Nine received encorafenib plus binimetinib.…”
Section: Anti‐ctla4 Anti‐pd1 Braf/mekimentioning
confidence: 99%
“…4,5 Carbonnel et al have reported a series of 10 consecutive patients hospitalised in their centre for severe colitis related to treatment with a combination of BRAF and MEK inhibitors for metastatic melanoma. 6 Nine received encorafenib plus binimetinib. Symptoms included diarrhoea, hematochezia and abdominal pain; all had ulcerations in the right colon with or without ileocaecal valve stenosis or lesions elsewhere in the colon.…”
Section: Editorial: Severe Colitis Induced By Targeted Therapies In D...mentioning
confidence: 99%